Project management perspective on UAV data collection: water management case study Baroch - Jech, Jakub; Jirava, Pavel (IEEE (Institute of Electrical and Electronics Engineers), 2023)
Currently, environmental protection is one of the main priorities. Vegetation cover as a complex system and water bodies are examples of land cover types that are observed and understood as important parts of our environment and need to be cared for. It is very important to collect up-to-date data on such systems. The use of unmanned aerial vehicles for data collection has become very used in recent years due to its scalability, efficiency, and instrumentality in various fields. Managing data collection projects using UAVs can be quite complex and challenging. This text examines the use of the Agile Scrum methodology in realization such a project.
Pohled projektového managementu na sběr dat UAV: water management případová studie Baroch
Keywords: data collection; drone; project management; scrum; UAV; sběr dat; trubec; projektový management; skrumáž; UAV